Prevalence and Antifungal Susceptibility of Candida parapsilosis Species Complex in Eastern China: A 15-Year Retrospective Study by ECIFIG - Guo, Jian; Zhang, Min; Qiao, Dan; Shen, Hui; Wang, Lili; Wang, Dongjiang; Li, Li; Liu, Yun; Lu, Huaiwei; Wang, Chun; Ding, Hui; Zhou, Shuping; et al. (Frontiers in Microbiology, 2021)
Candida parapsilosis complex is one of the most common non-albicans Candida species that cause candidemia, especially invasive candidiasis. This study was to evaluate the antifungal susceptibilities of both colonized and invasive clinical C. parapsilosis complex isolates to ten drugs: amphotericin (AMB), anidulafungin (AFG), caspofungin (CAS), micafungin (MFG), fluconazole (FLZ), voriconazole (VRZ), itraconazole (ITZ), posaconazole (POZ), 5-flucytosine (FCY), and isaconazole (ISA). Among the total of 884 C. parapsilosis species complex isolates, C. parapsilosis, C. metapsilosis and C. orthopsilosis accounted for 86.3%, 8.1% and 5.5% of the cryptic species respectively. The resistance/none-wild type rate of bloodstream C. parapsilosis to the drugs were 3.5%, of C. metapsilosis to AFG and CAS were 7.7%, of C. orthopsilosis to FLZ and VRZ were 15%, to CAS, MFG, and POZ were 5%. The geometric mean MICs of non-bloodstream C. parapsilosis for CAS (0.555 mg/L), MFG (0.853 mg/L), FLZ (0.816 mg/L), VRZ (0.017 mg/L), ITZ (0.076 mg/L), and POZ (0.042 mg/L) were significantly higher than those of bloodstream C. parapsilosis, for which the GM MICs were 0.464, 0.745, 0.704, 0.015, 0.061, and 0.033 mg/L respectively (P < 0.05). The MIC distribution of the bloodstream C. parapsilosis strains collected from 2019 to 2020 for VRZ, POZ and ITZ were 0.018, 0.040, and 0.073 mg/L, significantly higher than those from 2005 to 2018, which were 0.013, 0.028 and 0.052 mg/L (P < 0.05). Additionally, MIC distributions of C. parapsilosis with FLZ, and the distributions of C. orthopsilosis with ITZ and POZ might be higher than those in Clinical and Laboratory Standards Institute studies. Furthermore, a total of 143 C. parapsilosis complex isolates showed great susceptibility to ISA. Overall, antifungal treatment of the non-bloodstream C. parapsilosis complex isolates should be managed and improved. The clinicians are suggested to pay more attention on azoles usage for the C. parapsilosis complex isolates. Also, establishing the epidemiological cutoff values for azoles used in Eastern China may offer better guidance for clinical treatments. Although ISA acts on the same target as other azoles, it may be used as an alternative therapy for cases caused by FLZ- or VRZ-resistant C. parapsilosis complex strains.